Essential structure of orexin 1 receptor antagonist YNT-707, part III: Role of the 14-hydroxy and the 3-methoxy groups in antagonistic activity toward the orexin 1 receptor in YNT-707 derivatives lacking the 4, 5-epoxy ring. Issue 8 (15th April 2019) - Yamamoto, Naoshi; Ohrui, Sayaka; Okada, Takahiro; Saitoh, Tsuyoshi; Kutsumura, Noriki; Nagumo, Yasuyuki; Irukayama-Tomobe, Yoko; Ogawa, Yasuhiro; Ishikawa, Yukiko; Watanabe, Yurie; Hayakawa, Daichi; Gouda, Hiroaki; et al.
Graphical abstract: Abstract: Morphinan derivatives lacking the 4, 5-epoxy ring were synthesized to examine the participation of the 14-OH group, the 3-OMe group, and the aromaticity of the A-ring in the activity and selectivity for the orexin 1 receptor (OX1 R). The assay results and the conformational analyses of the 14-dehydrated and 14-H derivatives suggested that the orientations of the 6-amide side chain and the 17-benzenesulfonyl group would play important roles in the activity for OX1 R. In the 6β-derivatives, removal of the 3-OMe group and the reduction of the A-ring significantly decreased the activity toward the OX1 R, but these changes did not affect the 6α-derivatives. These results indicate that the 3-OMe group and the A-ring would be essential structural moieties for the 6β-derivatives.